92.6k views
1 vote
Evaluate the expression for k = –7 and m = –2. Km − m

User Ravit D
by
4.5k points

2 Answers

1 vote

Answer:


\tt 16

Explanation:


\tt km-m


\tt (k = -7, m=-2)

(First, for km - m substitute 'k' with '-7' and 'm' with '-2'):-


\tt \left(-7\right)\left(-2\right)-\left(-2\right)

⇒ (Multiply):-


\tt 14-\left(-2\right)
\tt a-\left(-b\right)= a+b


\tt 14+2

⇒ (Add):-


\tt 16

~

User Karan Kaushik
by
5.0k points
5 votes

Answer:

16

Explanation:

substitute k = - 7 and m = - 2 into the expression

km - m

= - 7(- 2) - (- 2)

= 14 + 2

= 16

User Jan Willem B
by
4.7k points